“Getting rid of systemic racism:” youth of color critical reflections and identified strategies during the twin pandemics - Gast, Melanie Jones; Bloomer, Rebecka; Brown, Aishia A. (Frontiers in Education, 2025)
Black, Latine, and Asian American young people living in the U.S. experienced the twin pandemics of COVID-19 and racism, along with racial traumas and stresses stemming from racial violence and public debates on how to (or not) address racism. Using critical consciousness and social justice youth development frameworks, this study sought to emphasize youth of color responses to the twin pandemics of COVID-19 and racism and youth-identified strategies for combating inequities experienced by these youth in Louisville, Kentucky. Between April 2021 to January 2022, youth of color (ages 12–24) were purposively recruited to engage in listening sessions. We conducted nine listening sessions on Zoom and face-to-face with 18 youth of color. Youth highlighted the saliency of racism and that they lacked safe spaces to share experiences, gain support, and collectively address and manage compounding issues. They described feeling dismissed by adults and excluded or removed from spaces where they could engage in collective care as a community. Youth suggested increased access to and existence of youth-centered spaces that prioritize youth voice and safety within the context of the COVID-19 pandemic and experiences with racism in Louisville. While past research often focuses on youth critical consciousness within afterschool programs or community organizations, our study explores the roles of COVID-19 and racism as dual pandemics and catalyzing events for youth in their building critical consciousness. Through their reflections and their suggested strategies, youth in this study engaged in critical reflection about racism during COVID-19 and moved between critical consciousness awareness at the self and community levels. Future research should explore mechanisms to identify youth strategies for collectivity both inside and outside formally organized programs.